Enhancing PIA Cake Entrepreneurs through MSME Strategy Training in the Digital Era: A Post-COVID-19 Priority - Supardi Supardi; Sriyono Sriyono; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article focuses on the post-COVID-19 priority of UMSIDA Community Partnership for PIA Cake Entrepreneurs in the Warurejo Gang Nangka area. The study aims to provide MSME strategy assistance in the digital era by offering training in production management, financial management, and marketing management. The methods involved conventional observations and expert consultation. The results indicate that the training significantly improved the entrepreneurs' creative thinking and operational, financial, and marketing management skills. The implications of this study underscore the importance of equipping small cake businesses with the necessary strategies to thrive in the digital economy, fostering economic growth and resilience in the global market. Highlight: Focus on Post-COVID-19 Priorities: The article emphasizes the significance of addressing the challenges faced by PIA Cake Entrepreneurs in the aftermath of the COVID-19 pandemic. MSME Strategy Training: The study highlights the importance of providing training in production, financial, and marketing management to enhance the skills and capabilities of small cake businesses in the digital era. Improved Entrepreneurial Skills: The results indicate a positive impact on the entrepreneurs' creative thinking and operational, financial, and marketing management skills, fostering their capacity to adapt and thrive in the global market. Keyword: Post-COVID-19, MSME Strategy Assistance, Digital Era, PIA Cake Entrepreneurs, Economic Growth